Worldwide Language Service Infrastructure Second International Workshop, WLSI 2015, Kyoto, Japan, January 22-23, 2015. Revised Selected Papers - Murakami, Yohei; Lin, Donghui; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book constitutes the refereed post-workshop proceedings of the Second International Workshop on Worldwide Language Service Infrastructure, WLSI 2015, held in Kyoto, Japan, in January 2015. The 4 full papers included in this volume and presented together with 2 short papers and 8 invited papers, were carefully reviewed and selected from 7 submissions. The papers are categorized into four parts: introducing metadata and annotations; providing technologies for language service platforms; atomic language services across different interfaces, policies, and development of language resources and services; and collecting reports on language service application.
Metadata and Annotation for Language Services -- Service Platform and Service Management -- Developing Language Resources and Services -- Language Service Applications.
Keywords: Computer science; Information storage and retrieval; User interfaces (Computer systems).; Artificial intelligence; Computational linguistics; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Language Translation and Linguistics; User Interfaces and Human Computer Interaction; Information Storage and Retrieval; Computational Linguistics; Electronic books